Development and Performance Evaluation of an Exhaled-Breath Bioaerosol Collector for Influenza Virus - McDevitt, James J.; Koutrakis, Petros; Ferguson, Stephen T.; Wolfson, Jack M.; Fabian, M. Patricia; Martins, Marco; Pantelic, Jovan; Milton, Donald K. (Aerosol science and technology, 2013)
The importance of the aerosol mode for transmission of influenza is unknown. Understanding the role of aerosols is essential to developing public health interventions such as the use of surgical masks as a source control to prevent the release of infectious aerosols. Little information is available on the number and size of particles generated by infected persons, which is partly due to the limitations of conventional air samplers, which do not efficiently capture fine particles or maintain microorganism viability. We designed and built a new sampler, called the G-II, that collects exhaled-breath particles that can be used in infectivity analyses. The G-II allows test subjects to perform various respiratory maneuvers (i.e., tidal breathing, coughing, and talking) and allows subjects to wear a mask or respirator during testing. A conventional slit impactor collects particles greater than 5.0 μm. Condensation of water vapor is used to grow remaining particles, including fine particles, to a size large enough to be efficiently collected by a 1.0 μm slit impactor and be deposited into a buffer-containing collector. We evaluated the G-II for fine particle collection efficiency with inert particle aerosols and evaluated infective virus collection using influenza A virus aerosols. Testing results showed greater than 85% collection efficiency for particles greater than 50 nm and influenza virus collection comparable with a reference SKC BioSampler®. The new design will enable determination of exhaled infectious virus generation rate and evaluate control strategies such as wearing a surgical-type mask to prevent the release of viruses from infected persons. Copyright 2013 American Association for Aerosol Research